Pengaruh Suhu Dan Lama Simpan Terhadap Angka Lempeng Total Pada Susu Kedelai Home Industry - Tiara Dini Harlita; H. Azhari; Poppy Risvina (CV. Wadah Publikasi Cendekia, 2023)
Soy milk is plant-based milk made from soybean seeds. The high protein content in soy milk can make milk a very favorable medium for microorganisms to grow and develop. The purpose of this study was to determine the effect of temperature and storage time on the total plate number of home industry soy milk in the city of Samarinda. This type of research is experimental research, using the Total Plate Count (ALT) examination method. The sample of this research is 2 samples. Each 1 sample of home industry soy milk was treated 3 times with 3 times and 2 temperatures, because there were 2 samples, 36 experimental units were carried out, each of which was diluted 3 times, the total treatment was 108 experimental units. Sampling using purposive sampling technique. The data analysis used is One Way Anova. Based on the research that has been donethere was an interaction effect between temperature and time on bacterial growth activity in soy milk samples A and B (f hit > F tab) or p value <0.05.From the results of the research that has been done, it can be concluded that if soy milk is not consumed immediately, it should be stored at a cooler temperature such as a refrigerator. The minimum limit for storing soy milk at room temperature is 2 hours, while at refrigeration temperature is 6 hours.